A longitudinal and comparative analysis of competitive balance in five European football leagues. Issue 5 (18th April 2018) - Ramchandani, Girish; Plumley, Daniel; Boyes, Sophie; Wilson, Rob
Abstract : Purpose: This paper aims to provide empirical evidence on competitive balance in the "big five" European football leagues, namely, the English Premier League, French Ligue 1, German Bundesliga, Italian Serie A and Spanish La Liga. Design/methodology/approach: This paper uses recognised measures of competitive balance to measure levels of concentration (within-season competitive balance) and dominance (between-season competitive balance) in the selected leagues over 22 seasons between 1995/96 and 2016/17. Findings: French Ligue 1 emerged as the most balanced league in terms of both concentration and dominance measures. The analysis also points to a statistically significant decline in competitive balance in all leagues apart from Serie A (Italy). Originality/value: The findings of this study are of concern for the league organisers. Competition intensity is a key component of a sport league, and a league that is dominated by one or a select few clubs is less attractive within the marketplace. This paper presents challenges at the league governance level for the five leagues examined.